Feline sacroiliac luxation: comparison of fluoroscopy-controlled freehand vs. computer-navigated drilling in the sacrum—a cadaveric study - Kleiner, Lukas; Wolf, Nicole; Precht, Christina; Haenssgen, Kati; Forterre, Franck; Düver, Pia (Frontiers in Veterinary Science, 2025)
IntroductionSacroiliac luxation is a common traumatic feline injury, with the small size of the sacral body being a challenge for surgical stabilization. This study compared an innovative computer-guided drilling method with the conventional fluoroscopy-controlled freehand technique. Neuronavigation, using CT-based planning and real-time tracking, was evaluated against the freehand method for accuracy and time efficiency.Materials and methodsBilateral sacroiliac luxation was induced in 20 feline cadavers. One side of the sacral body was drilled using fluoroscopy, and the other with neuronavigation (Stealth Station S8). A reference frame was affixed to the sacral spinous process for tracking. Ten cats were operated on by an ECVS diplomate and 10 by a resident. Postoperative cone beam CT images were used to assess both techniques, comparing the accuracy of the planned corridor vs. the actual drill hole in the sacrum. A learning curve for both methods was estimated by measuring procedure time.ResultsCT scan assessments showed all 40 drill holes achieved “surgically satisfactory” results. The computer-navigated technique demonstrated an average deviation of 1.9 mm (SD 1.0 mm) at the entry point and 1.6 mm (SD 0.8 mm) at the exit point. The pins of 3/20 reference frames penetrated the vertebral canal, creating a risk for potential clinical complications. The neuronavigation-guided procedures took an average of 23 min and 37 s (SD 8 min 34 s), significantly longer than the freehand technique, which averaged 9 min and 47 s (SD 3 min 26 s). A steep learning curve was observed with neuronavigation.DiscussionThe neuronavigation-guided technique achieved accuracy is comparable to the fluoroscopy-controlled method, is offering real-time feedback and has potential for highly precise surgeries near critical anatomical structures. However, significant attention must be given to the placement of the reference frame, as it is placed blindly and presents a potential risk for errors and complications. Despite its longer duration, the neuronavigation method shows promise for improving precision in complex surgical scenarios.